Protection of Indonesian Fishermen from China's Threat in the North Natuna Sea Region During the Covid-19 Pandemic - Angkasari, Wildani; Sujatmoko, Andrey (KnE Social Sciences, 2022)
The economic importance of the North Natuna Sea is premised not only on its function as one of the largest marine sources in Indonesia but also as an important location for the Indonesian military to conduct large-scale exercises. Amidst the ongoing outbreak of the COVID-19 pandemic, unauthorized fishing by Chinese flagged boats continues to be pervasive in the Indonesian EEZ off Natuna Islands. Chinese coast guard and military vessels were constantly and visibly present in those waters, testing the patience and perseverance of Indonesia’s authorities. The purpose of this article is to find out the cause related to the problem of protecting Indonesian fishermen in catching fish in the region. The Indonesian government is committed to ensuring rapid mobilization of its military and naval assets in the area when required to protect the fishermen. The method used in this research employed the qualitative method and critical content analysis. The legal consequences of ratifying the United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982) with Law No. 17 of 1985 concerning the ratification of UNCLOS, Law No. 32/ 20014 concerning about the sea are the substance of law regulation. The type of data used is secondary data, namely data obtained through literature study. The study matches that Indonesia must develop fishermen with the spirit of defending the country, especially in areas where the waters are partially located within China’s nine-dash line. Keywords: fisherman, North Natuna Sea, Covid-19 pandemic